Creating the not so big house : insights and ideas for the new American home - Susanka, Sarah. frey50 (Newtown, CT : Taunton Press ; [Emeryville, CA] : Distributed by Publishers Group West, 2000)
Offers a look at twenty-five examples of small designs to show readers what they need to know to plan the home that best fits their goals and lifestyles.
Introduction --The language of the not so big house -- Inside the not so big house -- A timeless classic (Rhode Island) -- A house for today and tomorrow (California) -- The essence of home (Pennsylvania) -- Doing more with less (Connecticut) -- A farmhouse for our time (Minnesota) -- A jewel in the suburbs (Illinois) -- Three easy pieces (Wisconsin) -- A sense of flow (Washington) -- A house in harmony (Massachusetts) -- Affordable comfort (Massachusetts) -- Comfort, pueblo-style (New Mexico) -- Thinking outside the box (California) -- Playfully sustainable (Vermont) -- One phase at a time (Maine) -- Updating, a not so big house (Connecticut) -- Tight quarters (New York) -- Southern comfort (South Carolina) -- An accessible house for one (Washington) -- A place of cool remove (Texas) -- Elegant simplicity (Rhode Island) -- Upstairs, downstairs (California) -- A not so big remodel (Connecticut) -- A cottage community (Washington) -- Creating the dream house (Minnesota) -- The whole nine yards (Minnesota) -- Afterword: The plan for the houses -- Architects and designers.
Includes index.
Keywords: Architecture, Domestic -- United States; Architecture -- United States -- History -- 20th century; Space (Architecture); Interior architecture -- United States